Die fetale Herzfrequenz unter der Geburt bei Hypoxie und Azidose – Eine computergestüzte Analyse - Roemer, V. M.; Walden, R. (Zeitschrift für Geburtshilfe und Neonatologie, 2013)
Using the naked eye, evaluation of fetal heart-rate (FHR) patterns remains difficult and is not complete. Computer-aided analysis of the FHR offers the opportunity to analyse FHR patterns completely and to detect all changes possibly due to hypoxia and acidosis. It was the goal of this study to make these hypoxic changes of the FHR visible and to compare them directly with normal tracings.During a period of 11 years the FHR signals (i. e., R-R intervals of the F-ECG) of 646 fetuses were recorded simultaneously also by a computer. The computer files were analysed thereafter, i. e., the obtained results had no immediate influence on the clinical management itself. To enter the study all fetuses must have been delivered by the vaginal route – in consequence without a significant loss of FHR signals. During forceps or vacuum deliveries recordings were continued. If necessary a new electrode was inserted. Recordings of fetuses with chorioamnionitis, tracings of malformed neonates and tracings shorter than 30 min were also excluded. No additional drugs were given to the mother during the time of recording. Thus 484 recordings were left. In this study only the last 30 min of each record were analysed off-line using our own computer programs written in MATLAB. Only 3 parameters were determined electronically: i) the mean fetal frequency (FRQ, bpm), ii) the number of turning points (N/min, see Fig. 1) in the FHR, which we called ‘microfluctuation’ (MIC) and iii) the oscillation amplitude of the FHR (OA, bpm, Fig. 1). Routine measurements of the acid-base variables from umbilical arterial (UA) and venous (UV) blood were performed using RADIOMETER equipments (ABL500) and trained personnel. To compare acidotic and non-acidotic FHR tracings, 2 pH groups were chosen: fetuses with a small non-acidotic “pH window” (pHUA=7.290–7.310) and 5 fetuses with severe acidosis, i. e., pHUA values <= 7.103.Using this narrow “pH-window” (7.290–7.310) shows that FRQ, MIC and OA belong together. The 3 variables are strongly associated with each other in a linear manner. All 3 correlation coefficients (r) are highly significant (P<0.001); in this context all 3 regressions seem to be linear. The mean pHUA in this special group amounts to 7.300±0.008 (N=50). In severe fetal acidosis (mean pHUA=7.051±0.060, N=5) MIC and OA are diminished significantly (P << 0.001) whereas the mean frequency is increased (ca.+6 bpm). Microfluctuation (MIC) seems to be the most sensible FHR parameter for the diagnosis of hypoxia and acidosis followed by OA and the fetal frequency niveau.In non-acidotic fetuses MIC, OA and FRQ belong together and their association can be described by the 3 basic principles presented above. Fetal reaction patterns during hypoxia and severe acidosis differ significantly when compared with tracings of non-acidotic fetuses. Computer-analysis reveals that MIC is the most sensitive FHR variable concerning hypoxia and acidosis followed by OA and the mean FRQ niveau. (Some of the acidotic recordings together with the WAS-score can be observed in full length at www.fhr-monitoring.org.)
Keywords: computeranalysis; microfluctuation; oscillationamplitude; fetal heart frequency; acidotic and non-acidotic fetuses